2015
DOI: 10.1007/s12094-015-1328-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and toxicity of helical tomotherapy for patients with locally recurrent nasopharyngeal carcinoma

Abstract: Reirradiation with HT in patients with LRNPC is feasible and yields encouraging results in terms of local control and overall survival with acceptable toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Of the 55 studies for which full texts were reviewed, 43 were excluded as they were irrelevant or did not meet the inclusion criteria (see Figure ). We identified 12 studies, including 1768 patients (Table ) . Of the studies included, 11 were from China and 1 was from Spain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 55 studies for which full texts were reviewed, 43 were excluded as they were irrelevant or did not meet the inclusion criteria (see Figure ). We identified 12 studies, including 1768 patients (Table ) . Of the studies included, 11 were from China and 1 was from Spain.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 12 studies, including 1768 patients (Table 1). [18][19][20][21][22][23][24][25][26][27][28][29] Of the studies included, 11 were from China and 1 was from Spain. Two studies were RCTs, 1 was a retrospective cohort study, 1 was a case control study, and the remaining 8 were single-institutional retrospective case series.…”
Section: Results Of Search Strategy and Characteristics Of Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective improvement of the CI and HI of the target area could reduce radiotherapy related side effects, thereby improving the quality of life of patients after radiotherapy is the major concern in the treatment of nasopharyngeal carcinoma in current clinical practice. Puebla [11] conducted a study of 17 patients with locally advanced nasopharyngeal carcinoma who underwent HT radiotherapy and the results showed that HT had better target area CI and HI than conventional IMRT in dosimetry, which could result in signi cantly decreased dose exposure on the vital organs. Zhang et al [12] compared the Three-dimensional Conformal Radiotherapy (3D-CRT) plan with the HT plan dosimetry for patients with locally advanced nasopharyngeal carcinoma, and the results showed that the use of spiral tomography in HT can further improve the CI and HI of the target area, thereby achieving a better protection of normal tissue.…”
Section: Discussionmentioning
confidence: 99%